O caso Pérolas Negras: um olhar complexo sobre a relação entre futebol, jornalismo e fluxos migratórios contemporâneos - Machado, Francisco José Eboli (Universidade do Vale do Rio dos Sinos, 2018)
This research intends to understand how journalism works relating to complexity in reporting soccer. In these terms, we focused the narrative about Pérolas Negras participation in 2016’s Copa São Paulo. The methodological approach to the object produced five movements: four movements pointed to the research question. In the fifth we analyze twelve texts published in different websites. The theoretical perspective is founded on E. Morin's complexity paradigm (1984, 2010, 2015), applied to journalism studies by Mar de Fontcuberta (2006). Soccer as a complex social and cultural phenomenon means considering sports press role on building, reproduction and circulation of symbolic productions related to soccer in Brazilian society. Globalized context produced negative effects on soccer player profession and affected the contemporary migratory fluxes. Simultaneously, we verify the sport press constructing idealized images about soccer as an important instrument to social ascension. We also found several stereotypes and the use of common sense representations about Haiti and Haitians as victims. Finally, it is possible to sustain that majority of the articles analyzed just reproduces an hegemonic view without considering the complexity witch journalism could adopt in its productions.
Keywords: Jornalismo; Complexidade; Futebol; Fluxos migratórios contemporâneos; Haiti; Journalism; Complexity; Soccer; Contemporary migratory fluxes; Haiti; ACCNPQ::Ciências Sociais Aplicadas::Comunicação